2011
DOI: 10.1002/joc.2125
|View full text |Cite
|
Sign up to set email alerts
|

Air flow and stability indices in GCM future and control runs

Abstract: ABSTRACT:Indices have been used as indicators of synoptic-scale flow strength, shear vorticity, flow direction and static stability over Ireland and Britain. Changes in large-scale dynamic flow and static stability over the European region are expected because of shifting climate patterns, and investigation of how these indices change in future runs of global climate models allows us to estimate how this will affect storm frequency and intensity in the region. Analysis of frequency distributions shows an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several studies established a relation between thunderstorm probability of occurrence and specific convective parameters and their thresholds [e.g., Haklander and van Delden , 2003; Kunz , 2007]. This connection provides the basis for statistical analyses of long‐term variability including trends in the convective parameters over past [e.g., DeRubertis , 2006; Cao , 2008] and future decades [ Leslie et al , 2007; Van Klooster and Roebber , 2009; Marsh et al , 2009; Hanafin et al , 2011]. In summary, most studies found evidence for a slight increase in the convective potential of the atmosphere both for past and future.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies established a relation between thunderstorm probability of occurrence and specific convective parameters and their thresholds [e.g., Haklander and van Delden , 2003; Kunz , 2007]. This connection provides the basis for statistical analyses of long‐term variability including trends in the convective parameters over past [e.g., DeRubertis , 2006; Cao , 2008] and future decades [ Leslie et al , 2007; Van Klooster and Roebber , 2009; Marsh et al , 2009; Hanafin et al , 2011]. In summary, most studies found evidence for a slight increase in the convective potential of the atmosphere both for past and future.…”
Section: Introductionmentioning
confidence: 99%
“…Climate variables projected under A1B climate change scenario from a general circulation model (Hadley Centre coupled model (HadCM3)) for two time periods, i.e., 2021-2040 (denoted as 2030) and 2071-2090 (denoted as 2080), were obtained (IPCC, 2013). The A1B climate change scenario describes a future world with very sharp economic growth, with global population peaking in the mid-century and with rapid introduction of new and more efficient technologies (Hanafin et al, 2011). This scenario assumes balances across all sources of technologies (Prudhomme et al, 2010).…”
Section: Future Climate Change Scenariomentioning
confidence: 99%